CHARACTER VALUES IN MACAPAT SONG - Ellie Syafitri; Hanaan Rofiiqoh; Rifa Alimah; Muhamad Chamdani (Universitas Sebelas Maret, 2018)
The purpose of writing this article is (1) to examine the meanings that contained in the macapat song (2) to examine the values that found in the macapat song. Value is a benchmark that is considered true and a guide in community life in making a decision. The method that used in writing this article uses the literature study method. From the problems obtained, it can be concluded that there are character values from macapat mijil, kinanthi, dhandanggula, gambuh, durma, pangkur, and pocung. Character value is the quality of depicting human behavior that can be formed through education and the surrounding environment. The character values that can be taken from the macapat songs are loving peace, religious values, educational values, honesty, responsibility, discipline values, and high curiosity. Through macapat songs, students can apply the character values in daily life.